2012
DOI: 10.1371/journal.pone.0035670
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Leishmania donovani Protein Disulfide Isomerase as a Potential Immunogenic Protein/Vaccine Candidate against Visceral Leishmaniasis

Abstract: In Leishmania species, Protein disulfide isomerase (PDI) - a redox chaperone, is reported to be involved in its virulence and survival. This protein has also been identified, through proteomics, as a Th1 stimulatory protein in the soluble lysate of a clinical isolate of Leishmania donovani (LdPDI). In the present study, the molecular characterization of LdPDI was carried out and the immunogenicity of recombinant LdPDI (rLdPDI) was assessed by lymphocyte proliferation assay (LTT), nitric oxide (NO) production, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 72 publications
0
23
0
Order By: Relevance
“…Kushawaha et al (48, 50, 51) studied the immunogenicity of LelF-2, TPI, and PDI of L. donovani in PBMCs of cured Leishmania -infected patients and hamsters where they found Thl-type cytokine profile (production of IFN-γ, IL-12, and TNF-α but not IL-4 or IL-10) with a remarkable increase in IgG2 and considerable protection. Gupta et al (49, 53) reported p45, enolase, and aldolase as a potential vaccine candidate with considerable prophylactic efficacy to the tune of 85–90% with an increased mRNA expression of iNOS, IFN-γ, TNF-α, and IL-12 and decrease in TGF-β and IL-4.…”
Section: Molecular Approaches To Leishmania Vaccine Developmentmentioning
confidence: 99%
“…Kushawaha et al (48, 50, 51) studied the immunogenicity of LelF-2, TPI, and PDI of L. donovani in PBMCs of cured Leishmania -infected patients and hamsters where they found Thl-type cytokine profile (production of IFN-γ, IL-12, and TNF-α but not IL-4 or IL-10) with a remarkable increase in IgG2 and considerable protection. Gupta et al (49, 53) reported p45, enolase, and aldolase as a potential vaccine candidate with considerable prophylactic efficacy to the tune of 85–90% with an increased mRNA expression of iNOS, IFN-γ, TNF-α, and IL-12 and decrease in TGF-β and IL-4.…”
Section: Molecular Approaches To Leishmania Vaccine Developmentmentioning
confidence: 99%
“…In agreement with these observations, PDI in the form of DNA vaccine has been shown to down regulate the expressions of IL-10 and IL-4 mRNA levels in hamsters as compared with infected controls [71]. As a potential vaccine antigen, PDI has shown good prophylactic potential along with robust immune responses in vaccinated animal against visceral form of disease [72]. …”
Section: Development Of Vaccinementioning
confidence: 79%
“…Recent studies have obviously characterized L. donovani PDIs as important protein for the design of new drug or vaccine against Leishmania parasites. In this species two groups have reported a 15 kDa atypical PDI with only one catalysing site "CGHC" [23] and a 55 kDa PDI [19]. Amit et al 2014 showed that protein of 15 kDa PDI promoted L. donovani infection, rendering macrophages more toxic which up regulates immunosuppressive factors such as IL-10 and causes retardation of anti-Leishmania activity of macrophage.…”
Section: Discussionmentioning
confidence: 96%
“…Previous results showed that PDI-2 was identified as one of the soluble leishmanial protein that induced a Th1 response in the PBMCs of Leishmania infected cured/endemic patients [18]. Further, rLdPDI-2 has been identified as a Th1 stimulatory and supposed to be the effector molecules for defense mechanism against Leishmania infection [19]. In this report, we described the isolation, cloning, sequencing, expression and characterization of the putative PDI-2 protein of L. tropica.…”
Section: Protein Overexpression and Purificationmentioning
confidence: 92%